PENGARUH LINGKUNGAN MASYARAKAT TERHADAP DEGRADASI MORAL REMAJA DI KAMPUNG RAWA BARU KELURAHAN SUKARAJA KOTA BANDAR LAMPUNG - Bagus Permana; Devi Sutrisno Putri; Abdul Halim; Ana Mentari; Karyadi Hidayat (Kampus Akademik Publiser, 2026)
Moral degradation among adolescents is an increasingly complex social problem resulting from weak social control within the community. In Kampung Rawa Baru, Sukaraja Village, Bandar Lampung City, this condition is marked by behaviors such as brawling, promiscuity, low levels of courtesy, and drug abuse among adolescents. The community environment encompassing social norms, parental supervision, role modeling, and social activities is believed to play an important role in shaping adolescent morality. This study aims to determine the extent to which the community environment influences the moral degradation of adolescents in the area. The method used is descriptive quantitative, with a sample of 52 respondents determined using the Slovin formula from a total population of 107 adolescents. Data were collected through questionnaires and analyzed using simple linear regression with the assistance of SPSS Version 22. The results show a negative and significant influence between a heterogeneous community environmentin a densely populated suburban area with weak social controland adolescent moral degradation, with a calculated t-value of 3.451 > t-table of 2.009 and a significance level of 0.001 < 0.05. The coefficient of determination of 19.2% indicates the influence of the community environment, while the remaining 80.8% is influenced by other factors not examined in this study.